Epoxy-Polyamide-Methyl Ethyl Ketone Laminate Systems Simulation On The Mechanical Properties - Abdul Aziz, Khairunnisa (Universiti Sains Malaysia, 2018)
Nowadays, finite element analysis (FEA) have become an interest in research industry. This is because advances in computer model development and simulation software facilitate physics-based explorations relying on the principles of mechanics. Due to the increased capabilities of solvers to accommodate and speedy simulations, the availability of algorithms to represent various physiological phenomena, and the development of user interfaces that bring model development to the masses, numerous contributions have been made through the broad use of modelling and simulation in research industry. In this research, the aim of this study is to develop simulation on the properties of epoxy laminate systems by using ANSYS simulation software. Previously, the investigation of low velocity drop impact tests on epoxy laminate systems are carried out by Du Ngoc Uy Lan on a research, ‘Investigation on The Properties of Epoxy-Polyamide-Methyl Ethyl Ketone Laminate Systems’ to determine the impact response. Therefore, for my final year project, the experimental results from the Lan’s research worked are required to develop simulation on the properties of epoxy laminate systems and to compare the experimental results obtained from the simulation process with results from experimental work. The aim of conducting dynamic FEA simulations was to closely model and compare the behaviour of the laminates that were tested using the direct impact experiments. The simulations were to be designed to provide an alternate means to validate the impact test results and recommend structural modifications if necessary.